IMPROVING VOCABULARY MASTERY USING DIGITAL PICTURE SERIES AT SLB HARAPAN IBU - Szalsza Surya Bella; Fenny Thresia; Yasmika Baihaqi (Journal of English Education and Entrepreneurship (JEEP), 2024)
The purpose of this research is to improving students vocabulary mastery using digital picture series media. The subject of this research were 3 students at eighth grades of SLB Harapan Ibu. The researcher was conducted by using classroom action research (CAR) with 4 steps namely : planning, action, observing, and reflecting that consist of 3 cycles. The analyzing data for quantitative was the students score of the tests. Based on the research that has been carried out, the percentages of students completeness in cycle I is 0%, in cycle II is 33% and in cycle III is 66%. Thus it can be concluded that by applying digital picture series media can improve the vocabulary mastery of mental retardation students at SLB Harapan Ibu. The digital picture series media can be used as an alternative to improve English vocabulary in SLB Harapan Ibu.